Health and illness in the neoliberal era in Europe - Gabe, Jonathan; Cardano, Mario; Genova, Angela (Bingley, U.K. : Emerald Publishing Limited, 2020)
Health and illness in the Neoliberal Era in Europe discusses the impact of neoliberalism on public health and the social construction of health and illness in Europe, analysing case studies at a European and national level. The book focusses on three main topics: health inequity, self-responsibilisation and organisational reforms. Increasing inequity is one of the main outcomes of neoliberal policy in Europe and here the authors examine the impact of neoliberal policies on health inequality, providing a European comparative data analysis of healthy life expectancy and mental health issues in Spain. The book looks at self-responsibilisation, as part of neoliberal citizenship, through topics such as crowdsourcing medicine and citizen science. Finally, it analyses organizational reform in Europe using three case studies: Italian national health care reforms, mental health policy in Italy and maternal care in Russia. The book includes contributions from the Czech Republic, Italy, Russia and Spain and fosters the development of sociological debate in such countries within a European framework. It presents quantitative data analysis as well as ethnographic research and outlines a complex scenario affecting the everyday life of European citizens, their health and illness.
Chapter 1. Neoliberal Epidemics: Etiology, A Bit Of History, And A View From Ground Zero; Ted Schrecker -- Chapter 2. Health Inequalities In Europe: Policy Matters In The Neoliberal Era; Angela Genova, and Simone Lombardini -- Chapter 3. Economic Crisis, Young Adults And Health In Spain; Marga Marí-Klose, Albert Julia, and Pedro Gallo -- Chapter 4. Citizenship, Neoliberalism And Health Care; Dino Numerato, Karel Cada, and Petra A. Honova -- Chapter 5. Crowdsourcing In Medicine In The Neoliberal Era; Linda Lombi, and Luca Mori -- Chapter 6. Adjusting Life To Illness Or Illness To Life? Reflections On Children's Competences In The Neoliberal Era; Anna Rosa Favretto, and Francesca Zaltron -- Chapter 7. Neoliberalism And Illness Narratives: The Intertwined Logics Of Choice And Care; Micol Bronzini, and Benedetta Polini -- Chapter 8. The Italian NHS Between Latent Paradoxes And Problematic Sustainability; Guido Giarelli -- Chapter 9. The Neoliberal Politics Of Otherness In Italian Psychiatric Care Notes On A Team Ethnography In Six Acute Psychiatric Wards; Mario Cardano, and Luigi Gariglio -- Chapter 10. Some Symptoms Of Neoliberalisation In The Institutional Arrangement Of Maternity Services In Russia; Anastasia Novkunskaya.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Public health -- Political aspects -- Europe; Neoliberalism -- Europe; Medical, Public Health; Public health & preventive medicine